Aid for Gender Equality and Development: Lessons and Challenges. (14th March 2016) - Grown, Caren; Addison, Tony; Tarp, Finn
Abstract: This UNU‐WIDER special issue of the Journal of International Development comprises a set of papers on the theme of aid and gender equality. While the topic of aid effectiveness has been examined in this journal and elsewhere, the focus on how well development assistance to countries and non‐governmental organizations promotes gender equality and empowers women is relatively new. This special issue is the first to marshal quantitative evidence and case studies on several themes: (1) macroanalyses of aid effectiveness and gender equality; (2) the determinants of aid for gender equality and women's empowerment; and (3) gender issues related to aid for education, health, land administration, fragile states and climate finance. © 2016 UNU‐WIDER. Journal of International Development published by John Wiley & Sons, Ltd.